Local electrical stimulation: introduction to the problem - Lev G. Agasarov; Maxim Yu. Yakovlev; Tatyana V. Konchugova; Larisa A. Marchenkova; Victor A. Drobyshev; Tatyana V. Apkhanova; Tatyana E. Belousova; Tatyana V. Marfina; Nadezhda V. Gushchina; Valeria A. Vasileva; Anastasia A. Mukhina; Irina A. Grishechkina; et al. (European Journal of Translational Myology)
The term "local electrical stimulation" means the delivery, for therapeutic purposes, of electric current signals in the areola of the projections of acupuncture points. Among the varieties of this effect are electro- and electroacupuncture, as well as transcutaneous electrical neurostimulation. In the case of electropuncture, minimal skin areas are irritated, outside of the damage, by placing the sensors according to the projections of the points. In the electroacupuncture, current signals are sent to steel needles immersed in tissues, ensuring the activation of not only skin afferents, but also deeper afferents. Percutaneous stimulation consists of irritating large areas of the skin with the help of portable devices. The paper reveals the mechanisms underlying the therapeutic effect of these methods, and puts forward an assumption about the prevailing biological significance of low-intensity stimuli. In addition, specific examples of use of local electrical stimulation in a number of pathological conditions are also presented.